2020
DOI: 10.1007/s11166-020-09340-7
|View full text |Cite
|
Sign up to set email alerts
|

The development of risk aversion and prudence in Chinese children and adolescents

Abstract: This study experimentally evaluates the risk preferences of children and adolescents living in an urban Chinese environment. We use a simple binary choice task that tests risk aversion, as well as prudence. This is the first test for prudence in children and adolescents. Our results reveal that subjects from grades 5 to 11 (10 to 17 years) make mostly risk-averse and prudent choices. The choices of 3rd graders (8 to 9 years) do not differ statistically from risk neutral benchmarks, but at the same time they ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 74 publications
(75 reference statements)
2
15
0
Order By: Relevance
“…In adolescents, most studies have not found any age effects on risk ( Sutter et al, 2019 ;, Eckel et al, 2012Munro and Tanaka, 2014 ), ambiguity 6 ( Sutter et al, 2013 ), nor prudence ( Noussair et al, 2014 ). Heinrich and Shachat (2018) showed a significant effect of school grade on prudent behavior, implying that prudence increased with age, but as the school type and level were not consistent over their sample, Trautmann and van de Kuilen (2018) indicated in their review on higher-order risk attitudes that these results should be interpreted with caution.…”
Section: Agementioning
confidence: 96%
See 3 more Smart Citations
“…In adolescents, most studies have not found any age effects on risk ( Sutter et al, 2019 ;, Eckel et al, 2012Munro and Tanaka, 2014 ), ambiguity 6 ( Sutter et al, 2013 ), nor prudence ( Noussair et al, 2014 ). Heinrich and Shachat (2018) showed a significant effect of school grade on prudent behavior, implying that prudence increased with age, but as the school type and level were not consistent over their sample, Trautmann and van de Kuilen (2018) indicated in their review on higher-order risk attitudes that these results should be interpreted with caution.…”
Section: Agementioning
confidence: 96%
“…This number is higher than in Sutter et al (2013 , 3 percent of multiple switchers in their adolescent sample) but much lower than 25% of inconsistent choices in Cardenas et al (2012) . Compared to adult samples, this percentage is very comparable ( Becker et al, 2012 ;Hogarth and Villeval, 2014 ). As multiple switches could indicate misunderstanding, we include multiple switchers as a categorical variable to our regression models and we re-ran all our main analyses on the sample of participants who only switch once.…”
Section: R = 1 − C E R /mentioning
confidence: 99%
See 2 more Smart Citations
“…While risk aversion has been studied extensively in this age group (Sutter et al, 2019), for prudence and temperance the evidence is scarce or non-existent. Heinrich and Shachat (2018) study prudence among 362 Chinese children and adolescents, aged 8 to 17 years, by counting the number of prudent decisions from three binary choice tasks. They investigate determinants of risk aversion and prudence and examine transmission of choices from parents to their children.…”
Section: Introductionmentioning
confidence: 99%